2009
DOI: 10.1094/mpmi-22-5-0529
|View full text |Cite
|
Sign up to set email alerts
|

Different Regulation and Roles of Lactonases AiiB and AttM in Agrobacterium tumefaciens C58

Abstract: The phytopathogen Agrobacterium tumefaciens C58 expresses two lactonases, AttM and AiiB. We showed that expression of the aiiB gene was controlled by agrocinopines A and B and required the agrocinopine-ABC transporter Acc, but was not affected by the level of quorum-sensing (QS) signal 3-oxo-octanoylhomoserine lactone (OC8-HSL). In the presence of agrocinopines, a constructed aiiB mutant accumulated OC8-HSL at a level 10-fold higher than that of the wild-type strain, and showed an exacerbated expression of a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 50 publications
2
76
0
1
Order By: Relevance
“…Initial studies described AttM as a lactonase induced in stationary phase that was responsible for termination of AHL-induced plasmid conjugation (65), but this may be a strain-specific pheonomenon (64). Additional studies have since indicated a specific role for AttM within the plant gall tumors characteristic of A. tumefaciens-mediated disease (63). AttM appears to contribute to bacterial fitness within the plant tumor (63) and may also function in interkingdom signaling between the plant and the bacterium.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies described AttM as a lactonase induced in stationary phase that was responsible for termination of AHL-induced plasmid conjugation (65), but this may be a strain-specific pheonomenon (64). Additional studies have since indicated a specific role for AttM within the plant gall tumors characteristic of A. tumefaciens-mediated disease (63). AttM appears to contribute to bacterial fitness within the plant tumor (63) and may also function in interkingdom signaling between the plant and the bacterium.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…Additional studies have since indicated a specific role for AttM within the plant gall tumors characteristic of A. tumefaciens-mediated disease (63). AttM appears to contribute to bacterial fitness within the plant tumor (63) and may also function in interkingdom signaling between the plant and the bacterium. Salicylic acid and the nonprotein amino acid GABA, both naturally found in plants, have been shown to induce attM expression (97)(98)(99), and overexpression of either of these compounds in plants increases the plant's resistance to A. tumefaciens infection (97,98).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…A. tumefaciens C58 derivatives carrying mutations in the Ti-plasmid had been previously constructed. They were: (i) C58 (pTi::Gm), that carries a gentamycin (Gm) cassette inserted into the atu6147 gene, which is not involved in virulence, fitness in plant tumor or opine pathways (Haudecoeur et al, 2009;Lang et al, 2013); (ii) C58 (pTi-nos::Km) that carries a kanamycin (Km) cassette inserted into the nos gene ( = atu6015), which is involved in the T-DNA-directed, nopaline synthesis in host plant; and, (iii) C58 (pTi-ocd::Gm) that contains a Gm resistance cassette inserted into the ocd gene ( = atu6016), which is involved in nopaline catabolism (Lang et al, 2014). We imposed artificial selection for modified opine assimilation as follows: to select for octopine assimilation ability in nopaline-type strains, overnight liquid cultures of nopaline-type A. tumefaciens C58 (pTi::Gm) and C58 (pTi-nos::Km) were washed three times, adjusted to OD 600nm = 1 and 3 ml of these cultures were plated onto agar AB medium (Chilton et al, 1974) containing 3 mM of octopine as sole source of carbon and nitrogen and incubated for 5 days.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…In A. tumefaciens, GABA acts as a signal that triggers gene expression (10,11). GABA-regulated functions contribute to moderate development of plant tumors and encompass the lactonase AttM, which inactivates the bacterial signal 3-oxo-octanoylhomoserine lactone (OC8HSL) 3 (12,13). However, free L-Pro, which also accumulates in infected plant tissues, blocks importation of GABA in the bacterial cells and hence blocks the GABA-induced degradation of OC8HSL and enhances the emergence of plant tumors (14,15).…”
mentioning
confidence: 99%